Al-Ghazali's Educational Thoughts as a Basis for Developing Character Education in Schools - Sulistia Ningrum; Muhtadi Abdul Mun’im (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
Character education is a very complex discussion in the world of education. Moral formation is a must for every individual. Character education is an important aspect in student development, because it does not only focus on academic achievement but also forms individuals who are moral and have noble character. Character education helps students develop values such as respect, responsibility, honesty, caring, and justice. This research aims to describe Al-Ghazali's thoughts as a basis for developing character education in schools and describe the concept of Al- Ghazali's thoughts on character education. The method used in this research is the library research method, namely a data collection method by understanding several literature related to research. The results of this research show that there is an instillation of moral values in schools which are based on Al-Ghazali's thoughts such as the values of honesty, self-control and simplicity.